Preclinical efficacy investigation of human neutrophil elastase inhibitor sivelestat in animal model of psoriasis - A. S. Zhukov; V. R. Khairutdinov; A. V. Samtsov; M. Krasavin; A. V. Garabadzhiu (Wiley, 2022)
Abstract Background Psoriasis is a chronic immune‐mediated inflammatory skin disease manifested by an increased rate of keratinocyte division. Currently, it has been established that the cytokines of the IL‐36 family play a significant role in the initiation and regulation of the inflammatory process in psoriasis. The IL‐36 cytokine found in skin is inactive and its activation requires proteolytic processing that may occur via the involvement of neutrophil serine proteases such as human neutrophil elastase (HNE). The localization of these enzymes in the upper layers of the epidermis suggests that topical application of HNE inhibitors could be efficacious in the treatment of psoriasis. Sivelestat is an HNE inhibitor developed for systemic use towards the treatment of acute respiratory failure. Aim The present study focussed on the investigation of the effects of sivelestat formulated for topical use, in the imiquimod‐induced model of psoriasis in mice. Methods The psoriasis‐like state was induced by application of imiquimod (Aldara®) 5% cream to mouse shaven skin. A group of 40 inbred mice of the BALB/c strain randomized into 4 groups of 10 was used in the experiment: Group 1 - no therapy (control), Group 2 - ointment (Vaseline) containing 1% sivelestat, Group 3 - cream (lanoline + olive oil + water in equal proportions) containing 1% sivelestat, Group 4 - 1% betamethasone dipropionate. Dermatological assessment of skin lesions was performed by means of the PASI method (mPASI), as well as histological and immunohistochemical evaluation. Results Based on the evaluation of efficacy manifestations, it was established that the total mPASI index value decreased by 50% during therapy with sivelestat cream and by 36% during therapy with sivelestat ointment. Histological study revealed that the epidermal thickness in groups that underwent therapy was 2.4-3.6 times lower compared to the control group. Immunohistochemical study of the skin indicated that following sivelestat treatment, the quantity of CD3+cells in the skin was 1.8-2.2 times lower, and the level of proliferative activity (Ki‐67+cells) was 2.3-2.9 lower compared to the non‐therapy group. In contrast to topical corticosteroids where the more pronounced anti‐inflammatory effect is typically seen with ointment formulations, with sivelestat we observed an opposite effect. The reasons for that reversal remain unclear. Conclusion Based on the results obtained using the animal model of imiquimod‐induced psoriasis, it was established that the HNE inhibitor sivelestat demonstrated efficacy comparable to that of a strong topical glucocorticoid steroidal drug (betamethasone dipropionate 1%). Significant resolution of skin lesions, reduction of epidermal thickness, diminishing of the skin infiltration with T‐lymphocytes and normalization of the cell division rate in epidermis and dermis were evident. Thus, suppression of IL‐36 mediated inflammation activity in the skin by topical application of a HNE inhibitor represents a promising new direction in the treatment of psoriasis. Certainly, HNE has other targets; thus, molecular studies could be subject of future experiments beyond the scope of the present study.